Pembuatan paving block berbahan dasar limbah plastik di Desa Tomoli Utara - Rendra Zainal Maliki; Shintami Rouwelvia Malik; Amalia Novarita; Asriana Sultan; Abdul Kadir Patta; Wahyu Rizki Firmansyah (Jurnal Dedikasi Masyarakat, 2025)
The main objective of this paving block production initiative is to address the waste problem in North Tomoli Village. The community was encouraged to work together to tackle waste issues and create a cleaner and more beautiful village environment. Waste management—particularly of plastic waste and similar materials—was the primary focus of the community service team in this activity. The method employed in this community service program was direct training provided to residents, conducted in three phases: the initial stage, the process stage, and the final stage. This training focused on the technical aspects of paving block production, with active community involvement throughout the process. Through this training approach, it is expected that the residents and village officials of North Tomoli will be able to manage waste in their surroundings independently. As a result, the volume of waste can be reduced and even transformed into products of economic value. The outcome of this community service activity indicates that the program was successfully implemented, and the community was able to produce paving blocks independently. With effective waste utilization and management, it is hoped that the residents can contribute to reducing environmental pollution in North Tomoli Village.